O ser e o dever ser do coordenador pedagógico em escolas públicas municipais de Fortaleza (CE): uma análise da dimensão ética do seu trabalho a partir dos pressupostos ontológicos do filósofo György Lukács - Sátiro, Charmênia Freitas de (2023)
The research's guiding axis of analysis is reflection on the Being and Duty-Being of the Pedagogical Coordinator in the Daily Life of Municipal Public Schools in Fortaleza (CE), taking as a basic reference the ontological assumptions of the philosopher György Lukács from his work Ontologia of the social being, in which he discusses issues related to work and ethics in human sociability. In this discussion, we included other authors to understand concepts. In this way, it is possible to reflect, based on the concepts of this work, about the specificity of the Pedagogical Coordinator's work in the public-school environment. From this perspective, work stands out in two horizons: as the genesis of social and professional life, constituting a condition of social and human existence, considered as a universal ontological category; and as a substance that supports the logic of capitalism, with its particularities, dynamics and objective conditions. In this articulation, the issue of ethics stands out as an essential element of human praxis and, therefore, as an elevation of human generosity. According to these considerations, the general objective of this research is to investigate the Being and Duty-Being of the Pedagogical Coordinator, identifying which daily actions, skills, training and objective conditions are necessary to carry out, in an ethical and competent manner, their duties as a worker in the environment school. From this general objective, specific ones emerge, namely: explaining the socio-historical dimension of social being, highlighting its ethical dimension; lecture about the ontological and ethical bases of the Pedagogical Coordinator’s work; highlight the Pedagogical Coordinator's praxis, identifying its ethical dimension between Being and Should-Be. Based on these objectives, we assume that, although we can identify ethical actions in the work of the Pedagogical Coordinator, he is unable to perform his functions in a fully ethical manner, whether for subjective or objective reasons, mainly with regard to the concrete conditions necessary to carry out their work. Therefore, it is necessary to understand the possibilities and limits between the Being and the Should-Be of the Pedagogical Coordinator. In connection with this issue, György Lukács' legacy on ethics is considered when considering man as the subject of his own history, the concepts present in his aforementioned work, the Being and Duty-Being of men, as well as when considering the ontological constitution of his ethical values in his daily work and the dialectical movement of this human praxis. To this end, we started from the foundations of historical-dialectical materialism, choosing as an instrument for data collection semi-open questionnaires with 10 municipal coordinators from Fortaleza, through which we proceeded to analyze the responses of the questionnaires, official documents that stipulate professional ethics, such as the Code of Ethics in the Public Service of Fortaleza, as well as the guidelines for the occupation and responsibilities of the aforementioned position. In the conclusions of this research, ethics was considered as a central mediation in the elevation of human humanity, therefore, capable of change, since the social being is rational and responsible for its actions with the capacity to reflect and change its actions when they are not They ethically serve the collective in their work and social life. Thus, ethical mediation constitutes the most important dimension of the contradictions of the position, making it possible to overcome what is in itself, towards the for-itself. In this overcoming lies the possibility of elevating human humanity. In the particular case of the Pedagogical Coordinator, in the materiality of school work in municipal public schools in Fortaleza, the initial thesis was confirmed: the work of the pedagogical coordinator is made up of multiple determinations, be they political, partisan, gender and formative, the which blocks, in a certain sense, the exercise of your work in a fully ethical way; There is, however, the possibility of overcoming these barriers and contradictions, typical of the position, which requires a constant struggle of resistance, training, studies and actions aimed at professional ethical action. Because, as the research confirmed, there is still no prescriptive code of ethics for the area of education, although just one code of ethics is not enough for full ethical action. This study also revealed contradictions between the Being and the Should-Be of these Coordinators, at the same time as it points to the possibility of overcoming this state of affairs through the ethical dimension.